Peran Sosial Media dalam Mewujudkan Keberlanjutan Usaha Melalui Keunggulan Kompetitif pada CV Goca Techno Abadi Jaya - Ni Putu Putri Ayu Wijayanthi; I Nyoman Dwi Arysna Mahendra (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The development of digital technology encourages service and technology companies to maximize the use of social media as a marketing strategy to maintain business sustainability amid increasingly intense competition. However, relying solely on social media does not automatically enhance business sustainability without the support of competitive advantage. This study aims to examine the effect of social media on business sustainability, with competitive advantage serving as a mediating variable at CV. Goca Techno Abadi Jaya. The research employs a quantitative approach with analysis using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The sample consists of 100 customers who are active social media users, selected through purposive sampling. The results indicate that social media has a positive and significant effect on both business sustainability and competitive advantage. Competitive advantage also demonstrates a positive and significant impact on business sustainability and acts as a partial mediator between social media and business sustainability. These findings highlight that an optimized social media strategy, combined with strengthened product differentiation and value proposition, can support the long-term sustainability of technology businesses.